Vision or illusion: The Northern Sea Route versus Suez Canal Route - Säteri, Fanni (2020)
This thesis studies the future of the Northern Sea Route and whether the Arctic route might benefit the Nordic countries so that Norway or Finland could become a new hub for cargo traveling from Asia to Europe. Research questions answered in this thesis: Is the Northern Sea Route a possibility for containership traffic? Can the Northern Sea Route replace the Suez Canal Route? Could the Nordic countries have a more significant role in international freight forwarding due to the Northern Sea Route? The data for the study was obtained from both primary and secondary sources. Primary data was collected through qualitative semi- structured interviews. The results suggest that the Northern Sea Route is being advertised as a shorter and faster route even though in reality it might not be shorter nor faster than the Suez Canal Route. When people talk about the Northern Sea Route they forget to mention the practicalities that currently make the route inefficient. Perhaps once the ice has thawed and ice- strengthened vessels are no longer required to navigate the route, the Northern Sea Route could be used more. The Northern Sea Route however will not replace the Suez Cannal Route. The Nordic countries benefiting from the does not seem likely. There are only vague theories about the Nordic countries benefiting Northern Sea Route and becoming hubs from the use of Northern Sea Route and the theories would work only when the route is ice free.